Bruno Schulz - Sklepy cynamonowe / A. Dworakowski ; Białostocki Teatr Lalek. - Dworakowski, Andrzej (1954- ). ([wydawca nieznany], 2008)
Plakat premiery 16.02.2008 r. Nazwisko autora przy lewej krawędzi u góry.